Speaker segmentation and verification - Zhong, Haishan (2008)
Speaker recognition has recently become popular in biometric security applications because voice is easier to obtain and speaker recognition is easier to apply remotely on networks or telephones. Speaker recognition can be classified into speaker iden-tification and speaker verification, as well as text-dependent and text-independent recognition.